ADVERSE EFFECTS OF RADIOACTIVE IODINE THERAPY IN THYROID CANCER SURVIVORS: IMPLICATIONS FOR QUALITY OF LIFE - Tabian, Rafael de Oliveira; Medeiros, Rodolfo de Oliveira; Padovan, Vitor Piacenti; Galhardi, Cristiano Machado; Gonçalves, Kayke Alexandre Sepero; Domingues, Lucas Ramos; Silva, Vinicius Willian Calderon da; Oku, Lyssa Miyagui; Reis, João; Nespolo, Hugo Henrique da Silva; et al. (INTERFERENCE: A JOURNAL OF AUDIO CULTURE, 2025)
Objective: This study aimed to analyze, through an Integrative Literature Review, the adverse effects of radioactive iodine (I-131) therapy in thyroid cancer survivors, with emphasis on psychosocial repercussions and quality of life after treatment. Method: The research was conducted in the PubMed, SciELO, Web of Science, LILACS, and Scopus databases, using controlled descriptors and free terms related to the topic. Articles published between 2015 and 2025 were included, in Portuguese, English, or Spanish, addressing physical and psychosocial effects of I-131 in thyroid cancer patients after medical discharge. The study selection followed PRISMA guidelines, and the data were systematized through a synthesis table, with methodological classification based on the Joanna Briggs Institute criteria. Results: Eleven articles were selected to compose the review corpus. The studies revealed a range of side effects associated with radioiodine therapy, such as salivary and lacrimal gland dysfunction, altered taste, chronic fatigue, and risk of secondary neoplasms. In the psychosocial domain, feelings of anxiety, insecurity, changes in body image, social isolation, and a perception of prolonged medicalization of life were highlighted. These findings indicate that surviving cancer does not necessarily equate to full well-being, requiring broader attention from healthcare services. Conclusion: Although effective from an oncological perspective, radioiodine therapy imposes long-lasting repercussions on patients’ lives. Recognizing the functional and subjective impacts as part of the therapeutic process is essential to ensuring quality of life, autonomy, and dignity throughout the thyroid cancer survivorship journey.